Iron Exchange and Prediction of Multiple Organ Dysfunctions in Sepsis - E. N. Barkova; Ye. V. Zhdanova; V. V. Kuznetsov; L. F. Balabanova; O. G. Sivkov (Общая реаниматология, 2007)
Objective: to define the mechanisms of impaired biological rhythms of iron exchange and lipid peroxidation (LPO) and to develop criteria for predicting the outcomes of pyoseptic complications.Subjects and methods. A hundred and seventeen patients with a good course of sepsis and its complication as multiple organ dysfunction (MOD) (a study group) and 108 healthy males (a control group) were examined. Twenty-four changes in the concentrations of total and ferrous iron (Fe2+) in the serum and urine, in those of OZhSS, malonic dialdehyde (MDA), MSM260 and MSM280 in the serum, urine, and red blood cells were studied.Results. With the good course of sepsis, iron exchange desynchronism was shown to be caused by elevated Fe2+ and MDA concentrations and enhanced proteolysis. The processes of renal MSM detoxification and elimination were ascertained to play an important role in the prediction of a good outcome of sepsis. With the poor course of sepsis and its complication as MOD, considerable rises in Fe2+, MDA, and MSM mesors were followed by their rhythm inversion and diminished MSM excretion due to progressive acute renal failure.Conclusion. The desynchronized exchange of iron was found to be due to the intensive increase in its fraction that triggers LPO and membrane destructive processes. On this basis, the authors have developed a procedure for predicting the course of sepsis and its complication as MOD, which allows the risk of complications and death rates to be substantially reduced during pyoseptic processes.